THE INFLUENCE OF PRICE, DIGITAL MARKETING, STORE ATMOSPHERE AND PRODUCT DIVERSITY ON PURCHASE DECISIONS - Lutfi, Muhammad; Satoto, Eko Budi; Izzudin, Ahmad (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
The clothing industry at Piala Tanggul Store has developed into a necessity for the community. One of the driving factors for the growth of consumers buying clothing products at Piala Tanggul Store lies in the clothing industry through price, Digital Marketing, Store Atmosphere and Product Diversity. This study aims to determine and analyze the effect of price, Digital Marketing, Store Atmosphere and Product Diversity on purchasing decisions at Piala Tanggul Store. This type of research uses a quantitative method with a sample size of 96 respondents and uses a non-probability sampling technique with a purposive sampling technique using a data collection technique in the form of a questionnaire to respondents. The data analysis technique for this study uses instrument testing, classical assumptions, multiple linear regression, hypotheses and coefficients of determination. The results of the analysis obtained show that price, digital marketing, store atmosphere and product diversity have a positive and significant partial effect on purchasing decisions, as well as a simultaneous effect.